0596 Sleep Disturbances in Cystic Fibrosis and Primary Ciliary Dyskinesia Over Time, Before and After Modulator Therapy. (25th May 2022) - Cohen-Cymberknoh, Malena; Lehavi, Maya; Atia, Ohad; Gileles-Hillel, Alex; Reiter, Joel
Abstract: Introduction: Prior studies have shown that cystic fibrosis (CF) and primary ciliary dyskinesia (PCD) are associated with sleep disturbances affecting quality of life (QOL).Our aim was to analyze changes in sleep complaints over time in patients with CF and pancreatic insufficiency (CF-PI), pancreatic sufficiency (CF-PS) and PCD, and explore the effect of CFTR modulators. Methods: Patients completed age-appropriate sleep quality questionnaires (SDSC, PSQI), quality of life questionnaires (PedQL, QOL-BE) and the Epworth sleepiness scale (ESS). They repeated the same questionnaires 3 years later. In addition, medical records were reviewed for clinical data. Results: Of a total of 50 patients, 27 were children and 23 were adults: 33 CF-PI, 8 CF-PS and 9 PCD. On the 3-year follow up questionnaires the PSQI revealed reduced sleep quality in 11 adult patients (47%), and the SDSC score was pathological, in 5 children (18.5%), suggestive of high rates of disturbed sleep. In children the mean SDSC score had not changed from baseline (41.1±11.5) to follow up (42.5±12.35; p=0.778). In adults the PSQI increased from 3.7±2.5 to 4.5±2.8 (p=0.075), most pronounced in adults that were not on modulators (3.9±2.7 to 4.8±3.4; p=0.027). This effect was driven primarily by changes in sleep initiation and maintenance domains. There were no other differences in the sleep complaints between CF-PI, CF-PS and PCD patients, or between patients on and off modulator therapy during the study period. Conclusion: Over time, quality of sleep worsened in patients with CF and PCD, particularly the ability to initiate and maintain sleep. Our results may suggest that modulator treatment attenuates the worsening of sleep complaints, however, larger studies are needed to clarify this. Support (If Any): None